PENGARUH PROMOSI KESEHATAN MENGGUNAKAN METODE KONSELING TERHADAP PENINGKATAN PENGETAHUAN IBU HAMIL TENTANG IMUNISASI DASAR DIWILAYAH KERJA PUSKESMAS TALAGA JAYA KABUPATEN GORONTALO - Dewi Modjo; Wiwi Susanti Piola; Ramiyatullah Ramiyatullah (Zaitun (Jurnal Ilmu Kesehatan), 2019)
This research was conducted in Talaga Jaya Health Center, Gorontalo District. The purpose of is to identify the effect of health promotion using counseling methods to increase pregnant women comprehension about immunization. The design of research was quasi one group pretest-posttest experiments. The population was all pregnant women with trismester I & II those are 98 people. The sample was 19 respondents. Health promotion was carried out 21 times in 3 weeks, an assessment of knowledge improvement before and after treatment using the Dependent T-test at a significance level of 95% (α = 0.05). The results showed an improvement of pregnant women comprehension before and after health promotion, with a p value of 0.001 <α-0.05. it can be concluded that there is an effect of health promotion using counseling methods to increase the comprehension of pregnant women about basic immunization.